1975
DOI: 10.1042/bj1460087
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of caffeine by tea-leaf extracts. Enzymic formation of theobromine from 7-methylxanthine and of caffeine from theobromine

Abstract: 1. Extracts prepared from tea leaves with Polyclar AT (insoluble polyvinylpyrrolidine) contained two methyltransferase activities catalysing the transfer of methyl groups from S-adenosylmethionine to 7-methylxanthine, producing theobromine, and to theobromine, producing caffeine. 2. The methyltransferases exhibited the same pH optimum (8.4) and a similar pattern of effects by metal ions, thiol inhibitors and metal-chelating reagents, both for theobromine and caffeine synthesis. Mg2+, Mn2+ and Ca2+ slightly sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 15 publications
4
38
0
1
Order By: Relevance
“…For more than 30 y, published studies have indicated that caffeine is produced via a single canonical pathway in plants (44,45 Caffeine biosynthetic network has 12 potential paths. The only path characterized from plants is shown by solid black arrows and involves sequential methylation of xanthosine at N-7, 7-methylxanthine at N-3, and theobromine at N-1 of the heterocyclic ring.…”
Section: Resultsmentioning
confidence: 99%
“…For more than 30 y, published studies have indicated that caffeine is produced via a single canonical pathway in plants (44,45 Caffeine biosynthetic network has 12 potential paths. The only path characterized from plants is shown by solid black arrows and involves sequential methylation of xanthosine at N-7, 7-methylxanthine at N-3, and theobromine at N-1 of the heterocyclic ring.…”
Section: Resultsmentioning
confidence: 99%
“…the origin of the purine ring in caffeine, until these methylating systems are demonstrated in vitro. In contrast, assuming that, by pathways analogous to those demonstrated for caffeine biosynthesis by Ogutuga & Northcote (1970), theophylline is synthesized from nucleic acids, it is possible that theophylline is produced from 1-methyladenylic acid, formed as a result of nucleic acid methylation and subsequent degradation, via 1-methylxanthine (Suzuki & Takahashi, 1975).…”
Section: Discussionmentioning
confidence: 97%
“…The 7-methylxanthosine found in this experiment was also identified after hydrolyzing to 7-methylxanthine, since the definite result for determination of the position of methyl group at the xanthine ring can be obtained by this method. The hydrolysis product matched 7-methylxanthine (Rf 0.40 in solvent (1) and 0.30 in solvent (5)). …”
Section: Resultsmentioning
confidence: 99%
“…Elution was done stepwise with O.oI, 0.05, 0.1, 0.2, and O.4M triethylammonium formate buffer (PH 3.8). The radioactive fraction corresponding to 7-methylxanthosine, which was eluted with 0.1 M buffer, was treated with 1 N HCl at 100°C for 1 hr and identified by co-chromatography with authentic methylated xanthines in solvent (1) and tertBuOH-methyl ethyl ketone-H20-28% NH40H (4: 3: 2: 1), solvent (5).…”
Section: Identification Of 7-methylxanthosine Produced By Feeding Witmentioning
confidence: 99%